Knowledge, dentist confidence and management of periodontal patients among general dentists from Belarus, Lithuania, Macedonia, Moldova and Romania - Jolanta Aleksejūnienė; Alina Pūrienė; Arunas Rimkervicius; Corneliu Amariei; Roxana Oancea; Tatiana Porosencova; Egor Porosencov; Julijana Nikolovska; Elena Mirnaya; Aleksandra Serova-Papakul; Kenneth A. Eaton (BMC, 2020)
Abstract Background Evidence concerning periodontal practice in Eastern European countries is scarce. The aim of the present study was to investigate periodontal risk knowledge, patient management and self-perceived confidence among General Dentists (GDs) from five Eastern European regarding their provision of periodontal care. Methods GDs from Belarus, Lithuania, Macedonia, Moldova and Romania participated in a questionnaire survey. Power calculations were used to identify the sample size for each country. The structured questionnaire included several domains of inquiry. The socio-demographic domain inquired about dentist's age, gender and years of clinical experience. The dental practice domain inquired about practice location, practising or not practising in a group practice and having or not having a periodontist or a dental hygienist in the practice. The distributions of answers across-countries were compared employing one way ANOVA (comparison of means) or Chi square test (comparison of proportions). For each country, the predictors of the study outcomes: a summative knowledge score for periodontal risks and dentist's confidence level were identified employing either linear or logistic multiple regression models. Results The sample comprised 390 Belarussian, 488 Lithuanian, 349 Macedonian, 316 Moldovan, and 401 Romanian GDs. The majority of GDs (~ 80%) practiced in urban areas. Age and gender distributions differed significantly among countries. Significant across-country differences were found regarding working/not working in a group practice, having/not having access to a periodontist/dental hygienist and in proportions of patients receiving periodontal treatments or being referred to specialists. None of Macedonian patients nor the majority of Moldovan patients (78%) were referred to periodontists. There were also significant across-country differences in diagnosis, patient management and periodontal knowledge. Only in the Lithuanian cohort were dentists' confidence levels associated significantly with their knowledge. In all countries, taking a medical history was a consistent and significant predictor of having higher periodontal knowledge score. Except in Belarus, periodontal risk assessment was a significantly consistent predictor of certainty levels associated with the provision of periodontal treatments. Conclusions There were substantial differences among GDs in the five countries regarding diagnosis, dentist's confidence and management of periodontal patients.